Complete genome sequence of a new chickpea chlorotic dwarf virus strain isolated from tomato in Kenya, obtained from llumina sequencing - Avedi, E.K.; Kilalo, C.D.; Olubayo, F.M.; Macharia, I.; Adediji, A.O.; Ateka, E.M.; Machuka, Eunice M.; Mutuku, Josiah M. (American Society for Microbiology, 2020)
High-throughput sequence analysis revealed the complete genome sequence of a novel, hitherto uncharacterized strain of Chickpea chlorotic dwarf virus (CpCDV) from tomato plants in Kenya. The sequence shared its highest nucleotide similarity (88.7%) with two CpCDV isolates from Burkina Faso.